The epidemiology of fecal carriage of nontyphoidal Salmonella among healthy children and adults in three sites in Kenya. - Esther M Muthumbi; Alfred Mwanzu; Cecilia Mbae; Godfrey Bigogo; Angela Karani; Salim Mwarumba; Jennifer R Verani; Samuel Kariuki; J Anthony G Scott (Public Library of Science (PLoS), 2023)
Background Despite the importance of non-Typhoidal Salmonella (NTS) disease in Africa, epidemiologic data on carriage and transmission are few. These data are important to understand the transmission of NTS in Africa and to design control strategies. Method To estimate the prevalence of stool carriage of NTS in Kenya, we conducted a cross-sectional study in Kilifi, Nairobi, and Siaya, sites with a low, moderate and high incidence of invasive NTS disease, respectively. At each site, we randomly selected 100 participants in each age-group of 0-11 months, 12-59 months, 5-14 years, 15-54 years and ≥55 years. We collected stool, venous blood (for hemoglobin and malaria rapid tests), anthropometric measurements, and administered a questionnaire on Water Access Sanitation and Hygiene (WASH) practices. Stool samples were cultured on selective agar for Salmonella; suspect isolates underwent serotyping and antimicrobial susceptibility testing. Result Overall, 53 (3.5%) isolates of NTS were cultured from 1497 samples. Age-adjusted prevalence was 13.1% (95%CI 8.8-17.4) in Kilifi, 0.4% (95%CI 0-1.3) in Nairobi, and 0.9% (95%CI 0-2.0) in Siaya. Prevalence was highest among those aged 15-54 years (6.2%). Of 53 isolates; 5 were S. Enteritidis, 1 was S. Typhimurium. No S. Typhi was isolated. None of the risk factors were associated with carriage of NTS. All isolates were susceptible to all antibiotics tested, including ampicillin, chloramphenicol, ciprofloxacin and co-trimoxazole. Conclusion Prevalence of fecal carriage was high in Kilifi, an area of low incidence of invasive NTS disease and was low in areas of higher incidence in Nairobi and Siaya. The age-prevalence, risk factors, geographical and serotype distribution of NTS in carriage differs from invasive disease.